Neuroimaging the emotional modulation of urge inhibition in Tourette Syndrome. (February 2021) - Bhikram, Tracy; Crawley, Adrian; Arnold, Paul; Abi-Jaoude, Elia; Sandor, Paul
Abstract: Tourette Syndrome (TS) is a neuropsychiatric condition characterized by tics that are typically preceded by uncomfortable urges that build until the tic is performed. Both tics and their associated urges are commonly exacerbated during states of heightened emotion. However, the neural substrates that are responsible for the development of urges have not been fully elucidated, particularly with regards to the influence of emotion. In this study, we investigate the brain areas associated with the development of urges and their modulation by emotion in patients with TS. Moreover, we explore the influence of obsessive-compulsive symptoms (OCS) which are commonly comorbid in TS. Forty patients with TS and 20 healthy controls completed an emotional blink suppression paradigm while undergoing functional magnetic resonance imaging. For the paradigm, participants completed alternating blocks of blink inhibition and free blinking while viewing pictures of angry and neutral facial expressions. Compared to controls, patients exhibited greater activity in the superior temporal gyrus and midcingulate during the inhibition of urges. Within the patient group, tic severity was associated with activity in the superior frontal gyrus during the angry inhibition contrast as compared to neutral; greater premonitory urge severity was associated with greater activity in the hippocampus, middle temporal gyrus and in the subcortex; blink inhibition ability was negatively associated with activity in the thalamus and insula. There were no significant associations with OCS severity for the emotion-related contrasts. The observed activated regions may represent a network that produces urges in patients, or alternatively, could represent compensatory cortical activity needed to keep urges and tics under control during emotional situations. Additionally, our findings suggest that OCS in the context of TS is similar to traditional obsessive-compulsive disorder and is neurobiologically dissociable from tics.